2016
DOI: 10.4187/respcare.04456
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Bronchoscopy Is Safe and Effective in Adult Subjects Supported With Extracorporeal Membrane Oxygenation

Abstract: BACKGROUND: Previous studies have demonstrated the safety of flexible bronchoscopy (FB) in mechanically ventilated subjects. However, the safety of FB in adult subjects receiving extracorporeal membrane oxygenation (ECMO) has not been described previously. METHODS: A retrospective review was conducted of all adult subjects who underwent FB while receiving ECMO support at the University of Alabama at Birmingham Hospital from January 1, 2013, to December 31, 2014. Physiologic variables, pre-and post-FB ECMO, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…However, Taha et al reported that malignancy was the most common indication in his study [ 10 ]. Western studies have conflicting results as some categorized malignancy as the most frequent indication [ 11 , 12 ], while others reported that pneumonia is the leading indication to proceed with bronchoscopy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Taha et al reported that malignancy was the most common indication in his study [ 10 ]. Western studies have conflicting results as some categorized malignancy as the most frequent indication [ 11 , 12 ], while others reported that pneumonia is the leading indication to proceed with bronchoscopy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…IC: infusión contínua. determinados por indicación de equipo tratante y se tomará en cuenta para búsqueda etiológica (14,15,16).…”
Section: Fibrobroncoscopía (Fbc) En Ecmounclassified
“…Specifically and in conformity to the management strategy in adults and infants with respiratory failure supported with veno‐venous ECMO , we suggest routine bronchoscopy with bronchial hygiene and review of correct positioning of the tracheal tube in all vaECMO cases. In our view, the patient should not be scheduled for weaning in the OR until the lungs have been adequately recruited and the lower alveolar system is clear.…”
mentioning
confidence: 92%
“…Weaning failure exposes the patient to avoidable perioperative stress, can result in significant depletion of patient functional reserves, and uses significant healthcare resources. Flexible bronchoscopy has been found to be both effective and safe in adult patients during ECMO . Bronchoscopy is known to improve both oxygenation and respiratory mechanics in patients with adult respiratory distress syndrome supported with ECMO .…”
mentioning
confidence: 99%